The clinical outcomes after surgical treatment of mass lesions causing sciatica - a single-center retrospective study - Okay Erhan (Serbian Medical Society, 2021)
Introduction/Objective. Sciatica is a disabling pathology with variable etiologies. The most common pathologies arise from discogenic or non-discogenic causes. Mass lesions are a rare cause of extraspinal sciatica, which have been commonly overlooked, leading to unnecessary spinal surgeries, delay in diagnosis or inadequate treatment. There is no standard surgical approach and functional outcomes after surgical treatment of these lesions are not well-known. The aim of this study is to evaluate clinical outcomes after surgical treatment of mass lesions causing sciatica in different locations. Methods. Data were obtained by a retrospective review from 2015 to 2020. The mean duration of symptoms at the time of surgery was 10.3 months (3–48 months). The mean age of patients at the time of surgery was 43.8 years (14–73 years). The mean follow-up was 19.5 months (4–50 months). In total, 14 cases had an extrapelvic localization distal to sciatic notch. The other three cases had lesions in the intrapelvic area, including left sciatic notch (1), right acetabulum (1), sacroiliac and lumbosacral region (1). None of the patients had palpable masses. Transgluteal, infragluteal, lateral, and posteromedial approach were used depending on location and size of the lesion. Results. At the final follow-up, all patients recovered with pain relief. The median musculoskeletal tumor society score was 90% (70–100). There was no recurrence at the latest follow-up. Conclusion. Our study demonstrated that early detection by neurological examination and radiological work-up can avoid unnecessary surgeries, enable early surgical treatment of tumoral mass with satisfactory clinical outcomes. The surgical approach should be individualized according to location and size of the lesion.